Występowanie aplikanta adwokackiego w postępowaniach przed organami podatkowymi i kontroli skarbowej - Rafał Bernat (Studia i Materiały)
The attorney-at-law can act independently as the attorney in tax proceedings and the tax audit or to grant the apprentice advocate the substitution. Indicating the scope of activities is a purpose of the article which the apprentice can make representing the taxpayer. Currently this matter separately isn’t settled and in the tax literature an interest in this subject isn’t being expressed. Analytical and linguistic-logical research methods were applied. The author made interpretation of legal texts by applying the linguistic, purpose, system interpretation but also referring to results of interpretation court and carried out by the revenue office. As a result of conducted examinations it is stated, the apprentice is authorized to make all action on behalf of the side in recalled proceedings with the shutdown of the ones assigned to professional attorneys (attorney-at-law, legal adviser, tax adviser) or of activities performed exclusively by the side. As the de lege lata postulate should be recognized, that applicable regulations in the sufficient way enable apprentice advocates to act as substitute on behalf of the taxpayer or controlled. Therefore, it is worthwhile so that attorneys-at-law more often refer cases of this type to apprentices and very apprentices displayed employing in purchasing both the technical knowledge and fiscal audit practical about tax and concerning matters.